Economic reform, trade and agricultural development - Goldin, Ian, 1955- (St. Martinʾs Press, 1993)
Focusing on the links between macroeconomic and agricultural reforms, this book examines, in a comparative perspective, these hitherto neglected but vital links, providing both theoretical and policy perspectives on the scope and sequencing of economic reforms.